2021
DOI: 10.3390/agronomy11081493
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Plants and Plant-Soil in Functionally Complex Mixtures including Grass Pea, Faba Bean and Niger, Intercropped with Oilseed Rape

Abstract: Winter oilseed rape (OSR) can be grown intercropped with frost-sensitive service plant mixtures. This practice may reduce weed pressure and contribute to providing N for OSR after service plant freezing. However, there is little knowledge of how plants interact together and with the soil in diverse annual crop mixtures. To assess these interactions, two contrasting legume service plants were selected: faba bean and grass pea, as well as a non-legume, the niger plant. OSR and the legumes were then grown in meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…Research on intercropping has shown that the best combination is when one of the species is from the Fabaceae family. Species from this family are "expected" to be able to create a large aboveground mass, have a strong root system with high absorption capacity, and have moderate nutrition requests, for example, they should be more adaptable to poorer soils and shaded conditions, with high weed suppression and an ability to fix atmospheric nitrogen even in competition conditions, as in intercropping [15][16][17]. Driven by photosynthesis, biological nitrogen fixation by legumes is a significant ecosystem service, which can partially meet the nitrogen needs of other crops in the system, and improve their overall productivity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Research on intercropping has shown that the best combination is when one of the species is from the Fabaceae family. Species from this family are "expected" to be able to create a large aboveground mass, have a strong root system with high absorption capacity, and have moderate nutrition requests, for example, they should be more adaptable to poorer soils and shaded conditions, with high weed suppression and an ability to fix atmospheric nitrogen even in competition conditions, as in intercropping [15][16][17]. Driven by photosynthesis, biological nitrogen fixation by legumes is a significant ecosystem service, which can partially meet the nitrogen needs of other crops in the system, and improve their overall productivity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Species from this family are "expected" to be able to create a large amount of aboveground mass, have a strong root system with high absorption power, and be moderate in nutrition requests e.g. adaptable to poorer soils, adaptable to shaded conditions, with high weed suppression and ability to fix atmospheric nitrogen [14][15][16]. Driven by photosynthesis, biological nitrogen fixation by legumes is a significant ecosystem service, which can partially meet the nitrogen needs of other crops in the system, and improve overall productivity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural products are also continuously and commonly utilized in multiple fields and systems for various purposes, including developing products necessary and important for engineering and medicines [6][7][8][9]. Fortunately, facilitated by the advent of next-generation DNA sequencing technology and rapid advancement in the multiple "omics" techniques, our knowledge of the interactions among crop plants, soil properties, and soil inhabitants has been significantly advanced from a wide range of perspectives [10][11][12]. Therefore, it is necessary and important to further strengthen the worldwide advancements of the molecular investigations of crop plants and their interactions with the surrounding environments, especially those based on genetic and genomic analyses, and to identify their effective applications and challenges.…”
mentioning
confidence: 99%